Heavy Metal Ion Detection from Whole Blood Using Ion Selective FET Sensor. (21st March 2018) - Wang, Shin-Li; Sukesan, Revathi; Hsieh, Ching-Yen; Wang, Yu-Lin
Abstract : Based on the idea of homecare diagnostics, we have developed a heavy metal ion sensor to detect lead ions in diluted blood, with high sensitivity, selectivity, wide dynamic range and great ease of operation. This FET based ion selective sensor consists of a high sensitivity FET, ion selective membrane and gold electrode. Using high field operation, the changes in ISM capacitance due to lead ion capture, is amplified by the FET and we can obtain a drain current signal that is proportional to the lead ion concentration in diluted blood. We can thus obtain high sensitivity and low detection limit, which is comparable to the traditional technologies such as ICP-MS (detection limit of Pb 2+ : 10 -10 M)